Doing : Red Dot design yearbook 2016/2017 - Zec, Peter, 1956- (Essen : Red Dot, 2016)
"Doing" showcases products from activity and lifestyle oriented areas such as garden, leisure, sport and games, babies and children, fashion, lifestyle and accessories, as well as watches and jewelery . Additionall, the design team of the year, as well as designer and jury portraits will be shown.
Text in English and German.
Keywords: Industrial design -- Periodicals